1999
DOI: 10.1209/epl/i1999-00443-7
|View full text |Cite
|
Sign up to set email alerts
|

Pauli susceptibility of nonadiabatic Fermi liquids

Abstract: Abstract. -The nonadiabatic regime of the electron-phonon interaction leads to behaviors of some physical measurable quantities qualitatively different from those expected from the Migdal-Eliashberg theory. Here we identify in the Pauli paramagnetic susceptibility χ one of such quantities and show that the nonadiabatic corrections reduce χ with respect to its adiabatic limit. We show also that the nonadiabatic regime induces an isotope dependence of χ, which in principle could be measured.When the Fermi energy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…This situation unavoidably leads to the opening of nonadiabatic channels in the electron-phonon pairing which we argue to play the primary role for the high values of T c in fullerene compounds. Finally, we stress the importance of peculiar nonadiabatic effects in both superconducting [11] and normal state properties [18,19] of fullerene compounds. Experiments in this direction are, therefore, of great interest.…”
Section: Nonadiabatic Channels In the Superconducting Pairing Of Fullmentioning
confidence: 94%
See 1 more Smart Citation
“…This situation unavoidably leads to the opening of nonadiabatic channels in the electron-phonon pairing which we argue to play the primary role for the high values of T c in fullerene compounds. Finally, we stress the importance of peculiar nonadiabatic effects in both superconducting [11] and normal state properties [18,19] of fullerene compounds. Experiments in this direction are, therefore, of great interest.…”
Section: Nonadiabatic Channels In the Superconducting Pairing Of Fullmentioning
confidence: 94%
“…Indeed, characteristic effects of the nonadiabatic vertex corrections are predicted to be observable in several quantities, such as T c and its isotope coefficient [9,10], the reduction rate of T c itself upon disorder [11], the effective electronic mass m ‫ء‬ [18], and the Pauli susceptibility [19]. A peculiar feature of the nonadiabatic processes is to produce, under some conditions, constructive electron-phonon interference in the particle-particle channel leading to an enhancement of T c [9,10].…”
Section: Nonadiabatic Channels In the Superconducting Pairing Of Fullmentioning
confidence: 99%
“…Hence, any evidence of electron-phonon effects on the Pauli spin susceptibility would be a direct proof of a nonadiabatic electron-phonon coupling [63,69]. The proper inclusion of the electron-phonon interaction in Eq.…”
Section: Phenomenology In Normal State: the Pauli Spin Susceptibilitymentioning
confidence: 98%
“…where m B is the Bohr magneton and G c is the total spin vertex function. It can be shown that the electron-phonon interaction in the Green's functions G and in the spin vertex G c cancels out in the adiabatic limit since the electron-phonon self-energy S ep in the presence of a magnetic field H has nonzero contributions only at a nonadiabatic level [67][68][69]:…”
Section: Phenomenology In Normal State: the Pauli Spin Susceptibilitymentioning
confidence: 99%
“…Therefore, following the same procedure reported in Ref. 11, we replace the electron-phonon interaction |g(k − k ′ )| 2 by its average over the Fermi surface:…”
mentioning
confidence: 99%